Microbial Succession in the Cheese Ripening Process-Competition of the Starter Cultures and the Microbiota of the Cheese Plant Environment - Korena, Kristyna; Krzyzankova, Miroslava; Florianova, Martina; Karasova, Daniela; Babak, Vladimir; Strakova, Nicol; Juricova, Helena (Microorganisms, 2023)
A large variety of cheeses can be produced using different manufacturing processes and various starter or adjunct cultures. In this study, we have described the succession of the microbial population during the commercial production and subsequent ripening of smear-ripened cheese using 16S rRNA gene sequencing. The composition of the microbiota during the first 6 days of production was constant and consisted mainly of LAB (lactic acid bacteria) originating from the starter culture. From day 7, the proportion of LAB decreased as other bacteria from the production environment appeared. From the 14th day of production, the relative proportion of LAB decreased further, and at the end of ripening, bacteria from the environment wholly dominated. These adventitious microbiota included Psychrobacter, Pseudoalteromonas haloplanktis/hodoensis, Vibrio toranzoniae, and Vibrio litoralis (Proteobacteria phylum), as well as Vagococcus and Marinilactibacillus (Firmicutes phylum), Psychrilyobacter (Fusobacteria phylum), and Malaciobacter marinus (Campylobacterota phylum), all of which appeared to be characteristic taxa associated with the cheese rind. Subsequent analysis showed that the production and ripening of smear-ripened cheese could be divided into three stages, and that the microbiota compositions of samples from the first week of production, the second week of production, and supermarket shelf life all differed.
Keywords: starter cultures; cheese microbiota; 16S rRNA gene sequencing; smear-ripened cheese